2019
DOI: 10.1016/j.jsames.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tides and seismicity in Northwestern South America: The case of Colombia

Abstract: We present the first systematic exploration of earth tides-seismicity correlation in northwestern South America, with a special emphasis in Colombia. For this purpose, we use a dataset of ~167,000 earthquakes, gathered by the Colombian Seismological Network between 1993 and 2017. Most of the events are intermediate-depth earthquakes from the Bucaramanga seismic nest and the Cauca seismic cluster. For this purpose, we implemented a novel approach for the calculation of tidal phases that considers the relative p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 69 publications
(143 reference statements)
1
14
0
Order By: Relevance
“…They do not use the TCFS criterion in their study. Moreover, and as we argued in our recent work (Moncayo et al, 2019), tidal phases have been improperly computed, especially in the case of the diurnal and monthly phases, in such a way that in most cases, including probably that of Cadicheanu et al (2014), the strong diurnal and monthly correlations we have observed, have been mostly absent. This paper is organized as follows: in Section 2 we start by describing the tectonic setting of the analyzed areas.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…They do not use the TCFS criterion in their study. Moreover, and as we argued in our recent work (Moncayo et al, 2019), tidal phases have been improperly computed, especially in the case of the diurnal and monthly phases, in such a way that in most cases, including probably that of Cadicheanu et al (2014), the strong diurnal and monthly correlations we have observed, have been mostly absent. This paper is organized as follows: in Section 2 we start by describing the tectonic setting of the analyzed areas.…”
mentioning
confidence: 58%
“…The Cauca seismic cluster is likely related to the subduction of Nazca beneath the North Andean Block (Cortes and Angelier, 2005;Chang et al, 2017). An in-depth analysis of the potential correlation between seismicity and earth tides in those clusters was carried out recently by Moncayo et al (2019), finding anomalously low values of the Schuster test p-values for the diurnal and monthly tidal components. Those findings motivated this follow-up investigation.…”
Section: Tectonic Setting Around the Seismic Clustersmentioning
confidence: 99%
See 3 more Smart Citations